أثر استخدام اسلوب التجارة الإلكترونية في تحسين أداء الشركات الصغرى والمتوسطة التي تديرها الرائدات الأعمال الليبيات دراسة تطبيقية على الرائدات الأعمال الليبيات في مدينة طرابلس (Comprehensive Journal of Science, 2025)
This study aims to determine the impact of utilizing e-commerce strategies on enhancing the performance of Small and Medium Enterprises (SMEs) managed by Libyan women entrepreneurs. The research specifically focuses on key performance indicators: revenue, growth rate, and access to new markets. The study's significance stems from the growing role of women entrepreneurs in the Libyan economy and their need for effective strategies to boost competitiveness.The research adopted a Descriptive Analytical approach, where primary data was collected through a questionnaire administered to a random sample of (50) Libyan women entrepreneurs who own and manage SMEs. Secondary data from relevant references and periodicals were also utilized. The responses of the participants were analyzed to test the hypotheses regarding the effect of investing in e-commerce on business performance.The statistical results confirmed a significant positive impact of e-commerce investment on all dimensions of improved business performance under investigation. Specifically, the findings indicated the following: First, investing in e-commerce positively affects revenue increase; second, it contributes to improving the companies' growth rate; and third, it leads to expansion and access to new markets. The entrepreneurs' responses showed a general degree of agreement with the relationship between the independent variable (e-commerce investment) and the dependent variable dimensions (improved business performance).The study concludes that e-commerce constitutes a pivotal strategic tool for empowering women-led SMEs in Libya, recommending the necessity of encouraging and supporting investment in digital infrastructure and skills to maximize this positive impact.